THE ROLE OF DIABETES MELLITUS, DYSLIPIDEMIA, AND SMOKING AS RISK FACTORS IN ACUTE ISCHEMIC STROKE INCIDENCE AMONG HYPERTENSIVE SUBJECT - Nurlia Nurlia (Faculty of Medicine, Hasanuddin University., 2016)
ABSTRACTIntroduction: Stroke is a leading cause of disability in the elderly, and the second leading cause of the death worldwide. This study aims to analyze the role of risk factors for diabe- tes mellitus (DM), dyslipidemia, and smoking in hypertensive patients who suffer an acute ischemic stroke. Methods: This study used a case-control design in hypertensive pa- tients who suffered an acute ischemic stroke as the case group, and hypertensive pa- tients without ischemic stroke as a control group. The samples were selected using the consecutive technique based on some inclusion criteria. Data were analyzed statistically with the Chi-Square test. The test results were considered significant if p <0.05. Further- more, logistic regression analysis was performed to find out the strength of the relation- ship with the odds ratio (OR). Layer analysis also conducted to validate the strength of dyslipidemia and smoking. Results: Among these three risk factors, diabetes had the most significant role (p <0.001) and it had 7-15 times stronger (Exp (B) 7.023; 95% CI3.205-15.394) to cause acute ischemic stroke in hypertensive subjects, compared to dyslipidemia and smoking. Conclusion: The results of the research indicated that all three of these risk factors play a role in causing acute ischemic stroke in hypertensive subjects compared to the control. Keywords: diabetes mellitus,dislipidemia, smoking, acute ischemic stroke, hypertensive subjects